Scattering for wave equations with dissipative terms in layered media - Mitsuteru Kadowaki; Hideo Nakazawa; Kazuo Watanabe (Electronic Journal of Differential Equations, 2011)
In this article, we show the existence of scattering solutions to wave equations with dissipative terms in layered media. To analyze the wave propagation in layered media, it is necessary to handle singular points called thresholds in the spectrum. Our main tools are Kato's smooth perturbation theory and some approximate operators.